УКРАЇНСЬКЕ ПОВСТАНСЬКЕ ЗАПІЛЛЯ ЯК ОБíЄКТ ІНТЕРЕСІВ ВІЙСЬКОВО-ПОЛІТИЧНИХ ЧИННИКІВ КІНЦЯ 1943ñ1944 рр. (Zaporizhzhia Historical Review, 2021)
The influence of certain enemy factors ñ the German invaders, polish, soviet partisans ñ on the functioning of rebellious rear is being determinated in the article. The range of changes of its quantity and quality indices: the region of extension, society spirits, the ability of population for pecuniary and financial help to the URA is being analysed.